Sistem Informasi Penjualan Bahan Bangunan (Studi Kasus :PT.Sinar Musi Jaya Palembang) - b41bul tujni (JUSIM (Jurnal Sistem Informasi Musirawas), 2017)
Abstract. The transaction of sale and purchase of goods is a system that provides information service of transaction data of sale and purchase of goods and stock of building material goods. This information system is important for the company. Company PT.Sinar Musi Jaya Palembang is where the object of writing sales transactions materials materials, information systems sales and purchases of goods on the company has not been well managed so often errors in the calculation of the amount of materials of stone coral and broken stone, in making reports such as reports broken stone, transaction report of purchase and sale, brownstone data processing report, customer processing report and supplier data report. The purpose of this study is to provide convenience for companies and employees in data processing sales transactions and purchase transactions, processing of broken stone materials, customer data processing and data processing suppliers, and simplify the report generation. This information system is built in order to provide convenience in data processing sales and purchases of materials both from sales to customers and purchases against suppliers and processing sales and purchase reports to be more precise and accurate. The conclusion in this paper to build information system sales and inventory of broken stone material is made by using the VB.NET programming language combined with Sql Server as database. Keywords: Sales Transaction, Purchase, Stock amount of goods, Information system, Vb.Net, Sql Server